Effects of L-carnitine supplementation on nutritional, immunological, and cardiac parameters in hemodialysis patients: a pilot study. Issue 1 (December 2015) - Sada, Haruki; Kato, Akihiko; Sumimoto, Ryo; Ohmori, Hiromitsu; Ohdan, Hideki
Abstract Background L-carnitine is an essential compound that facilitates the transport of long-chain fatty acid across the inner mitochondrial membrane for β-oxidation. However, the effect of L-carnitine supplementation remains to be fully explored in patients with chronic kidney disease. We aimed in this study to determine the multidirectional effects of L-carnitine supplementation on clinical parameters in more detail. Methods We orally administered L-carnitine to maintain serum-free carnitine levels within the normal range (30 to 70 μmol/L) for 6 months in 21 hemodialysis (HD) patients (age, 74 ± 11 years; time on HD, 60 ± 84 months). Results L-carnitine supplementation significantly increased serum transferrin from 155 ± 41 to 175 ± 48 mg/dL (p < 0.01) and retinol-binding protein from 8.9 ± 2.5 to 10.0 ± 3.4 mg/dL (p < 0.05). The triceps skinfold thickness was also significantly increased (p < 0.05), while the skeletal muscle mass in limbs and handgrip strength was not. L-carnitine enhanced natural killer (NK) cell activity at the E (effector cell)/T (target cell) ratio of 20:1 from 17.3 ± 14.1 to 20.8 ± 17.7 % (p < 0.01). In addition, L-carnitine improved left ventricular functional shortening (p < 0.01) with a significant decrease of brain natriuretic peptide (BNP) from 621.4 ± 666.8 to 412.0 ± 426.0 pg/mL (p < 0.05). Conclusions These findings suggest that oral L-carnitine treatment improves immunological and cardiac markers in HD patients. In contrast, L-carnitine did not change the skeletal mass-related parameters during the 6-month follow-up.